2021
DOI: 10.1111/ejh.13562
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of von Willebrand disease and pregnancy outcomes at regional Australian hospitals

Abstract: Background von Willebrand disease (vWD) is a heterogeneous hereditary bleeding disorder and is associated with risk of primary postpartum haemorrhage (PPH). Design and Methods An observational study at a tertiary referral centre in Australia of 16 women with 23 deliveries with a median age of 27.5 years (range, 21‐39; IQR = 9). Median gestational age at delivery was 39 weeks (range, 35‐41; IQR = 1.1). Results All cases had type 1 vWD, apart from one case with type 2. Patients were managed in combined obstetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The median APGAR score at 5 min was equal for infants born to women with VWD (9; IQR 9-9) and women without VWD (9; IQR 9-10). This finding is in agreement with an observational study by Wilson et al from Australia, who only included women with VWD (23 deliveries overall) and reported a median APGAR score at 5 min of nine [31].…”
Section: Discussionsupporting
confidence: 92%
“…The median APGAR score at 5 min was equal for infants born to women with VWD (9; IQR 9-9) and women without VWD (9; IQR 9-10). This finding is in agreement with an observational study by Wilson et al from Australia, who only included women with VWD (23 deliveries overall) and reported a median APGAR score at 5 min of nine [31].…”
Section: Discussionsupporting
confidence: 92%
“…15,33 The systematic review also highlighted high disease burden, with a high proportion of patients with VWD reporting a history of bleeding events. 23,28,31,34,37,39,[42][43][44][45]47,[54][55][56][57][58][59][60][61][62][63]67,68,[70][71][72][73] Patients with VWD were also reported to have lower/poorer HRQoL scores versus general populations, 77,80,82 as well as increased HCRU. 83,84 VWD prevalence estimates varied highly according to the study populations and method of estimation.…”
Section: Discussionmentioning
confidence: 99%
“…The studies reviewed suggest that HMB occurs frequently (>60%) in patients with VWD, 23,31,34,42,44,[54][55][56][57][58] while postpartum bleeding can occur in up to 13% of women with VWD. 42,47,50,[59][60][61][62][63] This systematic review also suggests that there are important gaps in VWD diagnosis that could delay care and result in adverse health outcomes. Although the time from symptom development to diagnosis was poorly documented in the literature, 38,52 the 3-year difference between median age at overt symptom onset and median age at diagnosis reported in this review 38 highlights the need for improved disease awareness for both patients and health care providers.…”
Section: Dovepressmentioning
confidence: 94%
See 2 more Smart Citations